P.R. Brahmananda. Growth/ess Inflation by Means of Stockless Money: A New Classical Treatise on Rising Prices. Bombay: Himalaya Publishing House. 1981. pp.xvi+471. Price: Rs.9S.00. (The Pakistan Development Review, 1982)
Traditionally inflation has been seen as a purely economic problem. In recent years studies have emphasized that the present day inflation is more than an economic problem. It has deep roots in the political and social systems which have strong connections with the economic mechanism of society. Inflation is analysed and conceptualized as :I problem in political economy. It is a worldwide phenomenon but it has become most pertinent in the case of developing countries where the socio-economic fabric of the society is far removed from that of the developed countries on whose experience the prevalent economic theories of inflation are based. As such when the theories completely divorced from reality are applied in the developing economies they aggravate the situation further. The book under review is free from this blemish as it examines the problem of inflation with reference to the socio-economic and political set-up of the developing countries in general and to the Indian situation in particular.